Réussir ses relations médias - Amour Joël Ombassa (Communiquer)
This book review discusses Réussir ses relations médias, edited by Jason Luckerhoff and Marie-Claude Lapointe and published in 2024 by the Presses de l’Université du Québec. This review highlights how this practical guide combines reflections on the changing media landscape with concrete advice on strategic communication. Drawing on case studies, sector-specific examples, and professional testimonies, the book offers tools to better understand and manage relationships with the media in a digital environment.